2012
DOI: 10.3851/imp2108
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum, Risk Factors and Outcome of Immune Reconstitution Inflammatory Syndrome in Patients with Tuberculosis–HIV Coinfection

Abstract: TB-IRIS was a frequent reason for clinical deterioration among patients with TB commencing ART but was not a primary contributor to mortality. Patients with advanced CD4 depletion and anaemia were at increased risk of TB-IRIS. Some patients developed late-onset TB-IRIS and/or a recurrent TB-IRIS episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
8
29
0
Order By: Relevance
“…An increased risk of both PR and IRIS has been identified in patients with disseminated or extrapulmonary disease, who are considered to have higher bacillary/antigen loads, although this may not necessarily be the case in patients with apparently isolated peripheral lymph node disease. 1,8,17,18,32 The risk of paradoxical IRIS has been demonstrated to be highest when HAART is initiated early during antimycobacterial therapy, at a point when mycobacterial loads are still nearmaximal. This risk has been confirmed in large RCTs seeking to optimize the timing of HAART initiation.…”
Section: Responses To Treatment Risk Factors and Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…An increased risk of both PR and IRIS has been identified in patients with disseminated or extrapulmonary disease, who are considered to have higher bacillary/antigen loads, although this may not necessarily be the case in patients with apparently isolated peripheral lymph node disease. 1,8,17,18,32 The risk of paradoxical IRIS has been demonstrated to be highest when HAART is initiated early during antimycobacterial therapy, at a point when mycobacterial loads are still nearmaximal. This risk has been confirmed in large RCTs seeking to optimize the timing of HAART initiation.…”
Section: Responses To Treatment Risk Factors and Pathogenesismentioning
confidence: 99%
“…In HIV-seronegative individuals, low baseline lymphocyte counts at the time of TB diagnosis are associated with an increased risk of developing PR, 2,8 whilst in HIV-seropositive individuals, low CD4+ T cell counts have been related to subsequent IRIS in a range of studies. 13,18,23,24,34 Advanced HIV disease has also been identified as a risk factor for IRIS, consequent on high pre-HAART HIV-1 viral loads. 34 Given that a relationship between active TB and lymphopenia has been reported, 42 and it is suggested that active TB is associated with a degree of immunodeficiency, 43 one could hypothesize that a baseline immunodeficient phenotype in both HIV seronegative and seropositive individuals is implicated in the development of both PR and IRIS.…”
Section: Responses To Treatment Risk Factors and Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Such patients undergo a unique and exuberant recovery characterized clinically by an inflammatory syndrome which is excluded by a typical drug reaction. In a recent study by Worodria et al [95], a total of 21% of 254 HIV-1/TB co-infected patients developed TB-IRIS within 2 weeks of starting HAART. It occurs in between 8 and 43% of co-infected patients and causes significant patient morbidity [96].…”
Section: Expert Opinionmentioning
confidence: 99%